Oxidative stress markers in infectious respiratory diseases: current clinical practice - Bwititi, P. T.; Chinkwo, K. (International Journal of Research in Medical Sciences, 2017)
Cases of some infectious respiratory diseases are on the increase and aetiology of these diseases is associated with assault from exogenous and endogenous oxidants. This requires constant appraisal on current knowledge hence this review looks at current knowledge on oxidative and nitrosative stresses in selected infectious respiratory diseases and the utility of stress biomarkers. A major metabolic or organic stress is oxidative stress; an imbalance between oxidants and anti-oxidants and it is implicated in aetiology of various diseases including respiratory diseases. Physiologically reactive oxygen and nitrogen species are beneficial since they take part in various cellular processes. During infection, the host produces reactive species to defend against invading pathogens but some microorganisms have mechanisms to defend against the reactive oxygen and nitrosative species produced by host. Hence, there is also the oxidative stress ‘pros and cons’ paradox in infectious respiratory disease, which makes careful interpretation of laboratory methods necessary. Although most reactive oxygen and nitrosative species are not very stable and cannot be measured directly, there are indirect assessment methods of oxidative stress or oxidants or anti-oxidants. Various biological samples such as exhaled air, exhaled breath condensate, sputum and blood are used in investigation and management of infectious respiratory diseases. Measurement of oxidative stress can be done using various laboratory methods including, chemical, immunoassays and chromatographic thus allowing oxidative stress assessment to be important in infectious respiratory diseases.